Polyamines and Legumes: Joint Stories of Stress, Nitrogen Fixation and Environment - Menéndez, Ana Bernardina; Calzadilla, Pablo Ignacio; Sansberro, Pedro Alfonso; Espasandin, Fabiana Daniela; Gazquez, Ayelén; Bordenave, César Daniel; Maiale, Santiago Javier; Rodríguez, Andrés Alberto; Maguire, Vanina Giselle; Campestre, Maria Paula; Garriz, Andrés; Rossi, Franco Rubén; et al. (Frontiers in Plant Science, 2019)
Polyamines (PAs) are natural aliphatic amines involved in many physiological processes in almost all living organisms, including responses to abiotic stresses and microbial interactions. On other hand, the family Leguminosae constitutes an economically and ecologically key botanical group for humans, being also regarded as the most important protein source for livestock. This review presents the profuse evidence that relates changes in polyamines levels during responses to biotic and abiotic stresses in model and cultivable species within Leguminosae and examines the unreviewed information regarding their potential roles in the functioning of symbiotic interactions with nitrogen-fixing bacteria and arbuscular mycorrhizae in this family. As linking plant physiological behaviour with "big data" available in "omics" is an essential step to improve our understanding of legumes responses to global change, we also examined integrative MultiOmics approaches available to decrypt the interface legumes-PAs-abiotic and biotic stress interactions. These approaches are expected to accelerate the identification of stress tolerant phenotypes and the design of new biotechnological strategies to increase their yield and adaptation to marginal environments, making better use of available plant genetic resources.